Relationships of lower extremity and trunk asymmetries in elite soccer players - Maly, T.; Hank, M.; Verbruggen, F. F.; Clarup, C.; Phillips, K.; Zahalka, F.; Mala, L.; Ford, K. R. (Frontiers in Physiology, 2024)
In light of previous research highlighting the prevalence of asymmetries in soccer players and possible links to injury risks, there is a crucial gap in the biomechanical understanding of complex relationships between lower extremity and trunk asymmetries in elite soccer players. The purpose of this study was to investigate the level, relationships, and differences among twelve different parameters of strength, morphological, and neuromuscular asymmetries in elite soccer players.